Utilization of E-Commerce in Sales Transactions of Goods and Services Products in the Autonomous Organization of Nasyiatul Aisyiyah Kudus Regency - Jauhar, Muhamad; Mundriyastutik, Yayuk; Nasriyah, Nasriyah; Dewi, Okta Yosiana; Pusparatri, Edita (Asosiasi Profesi Multimedia Indonesia, 2023)
Uncertainty at the time of the COVID-19 pandemic caused businessmen to suffer a decline in revenue. The entrepreneur must have a strategy to survive through the use of information technology. Digital marketing is very useful to support the development of a business or enterprise. When a business has been connected to the Internet automatically, the business will be connected with Internet users throughout the world. So, it will greatly help the business in promoting the product effectively and efficiently. The purpose of this community service is to increase interest in entrepreneurship through the use of e-commerce. Public service activities are carried out in the form of training on e-commerce use in transactions of sale and purchase of goods and services. This activity was carried out in August 2023 at the Director of the Nasyiatul Aisyiyah Branch (PCNA) district of Undaan. Target activities of 19 PCNA cadres. The method of conducting the activity is in the form of interactive lectures, question-and-answer discussions, and demonstrations. Entrepreneurial interest in using e-commerce evaluated using a questionnaire of 22 statement items (validity value 0.354-0.647 and reliability 0.789). Data analysis is interpreted in descriptive form. Public service results have shown that the majority of cadres have a good interest in entrepreneurship using e-commerce. Social media is an opportunity for Micro small and Medium Enterprises to compete in the local market. Each social media platform has its own advantages and uniqueness. The potential of social media bias supports brand, sales improvement, customer service and product development.